Hybrid meat products: the physicochemical and microstructural properties of beef meat emulsion produced with jackfruit (Artocarpus heterophyllus) flesh and bamboo (Bambusa polymorpha) shoot as meat substitutes - Bee Chi, Ng; Asyrul‐Izhar, Abu Bakar; Sani, Muhamad Shirwan Abdullah; Ismail‐Fitry, Mohammad Rashedi (John Wiley and Sons, 2024)
Hybrid meat products are a beneficial approach to incorporating plant proteins into conventional meat formulations, taking into account current market trends that emphasise the partial decrease in animal protein content. This study aimed to evaluate the effects of using different percentages of beef meat (BM), jackfruit flesh (JF) and bamboo shoot (BS) as a meat substitute in beef meat emulsion. Emulsion with 100% BM (Control), (A) 50% JF + 50% BM, (B) 50% BS + 50% BM, (C) 50% BM + 25% JF + 25% BS, (D) 100% JF and (E) 100% BS were developed. Six formulations of meat emulsion samples were prepared and analysed in terms of physicochemical and microstructure properties. The substitution of JF and BS in meat emulsion resulted in more stable emulsion stability. The WHC and pH values showed no significant differences (P > 0.05) between samples. The samples with different percentages of JF and BS had significantly increased (P < 0.05) the moisture content and the crude fibre content, however, it significantly reduced (P < 0.05) the crude protein content. No significant difference (P > 0.05) in ash and fat content for the formulated meat emulsions from the control. One hundred per cent BS showed higher lightness (L*), yellowness (b*) and lower redness (a*) values significantly (P < 0.05) compared to the control. One hundred per cent JF and 100% BS depicted significant differences (P < 0.05) for the textural properties and gel strength compared to the control. The scanning electron microscopy (SEM) provided evidence for the microstructure that the higher the percentages of plant-based ingredients, the smaller the cavities. Overall, the incorporation of 50% BM + 25% JF + 25% BS could produce the best-suited meat substitution product.